Collecting Infant Environmental and Experiential Data Using Smartphone Surveys. Issue 1 (January 2021) - Rosales, Marcelo R.; Rohloff, Peter; Vanderbilt, Douglas L.; Tripathi, Tanya; Valentini, Nadia Cristina; Dusing, Stacey; Smith, Beth A.
Abstract : We propose that the collection of infant experiential and environmental data using smartphone surveys has the potential to fill a gap in foundational and clinical knowledge. To achieve this, these data need to be collected in a systematic way that is translatable globally. We can then begin to understand differences in child development and physical therapy from a variety of cultures and traditions. An infant's development is shaped by experiences in everyday life, and everyday experiences vary around the world. Hence, it is important to quantify these experiences to better understand variability in developmental trajectories. Recent increase in smartphone access has made the capability of collecting infant experiential data more feasible around the world. We provide examples and suggestions for ways in which experiential and environmental data can be collected for future practice. Abstract : We propose that the collection of infant experiential and environmental data using smartphone surveys has the potential to fill a gap in foundational and clinical knowledge.